Practical Significance of Transrectal Doppler Ultrasonography and Ultrasonography in Prostate Cancer - Abdukadirovich, Rakmanov Xamza (Journal of Science in Medicine and Life, 2024)
Brachytherapy allows most patients to maintain potency and reduces the risk of urinary incontinence. But, again, there are a number of nuances that do not allow brachytherapy to become the "gold standard", some of which are: the impossibility of correctly staging the tumor process and determining the radicality of the treatment (there is no removed sample of the prostate and lymph nodes); the method is suitable only for patients with a minimal degree of the tumor process (not even all cases of local prostate cancer); restrictions on the size of the prostate gland - the procedure is not suitable for patients with severe urinary disorders (difficulty urinating, slow urine flow, frequent urination, strong urges, repeated night trips to the toilet, urinary incontinence departure etc.); The postoperative period is often complicated by problems such as acute urinary retention, which requires additional therapeutic measures.